Hadith #2244 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Awymr bin Ashqr al-Ansari al-Bdry; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
My daughter; she is weaned or about to wean. Rafi’ said: My daughter. The Prophet (ﷺ) said to him: Be seated on a side. And he said to her: Be seated on a side. He then seated the girl between them, and said to them: Call her. The girl inclined to her mother. The Prophet (ﷺ) said: O Allah! guide her. The daughter then inclined to her father, and he took her.
Grade: Sahih

Hadith #2245 - Sunan Abi Dawud - Abbas bin Sahl bin Sa'd عباس بن سهل بن سعد الساعدي; Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
Sahl bin Sa’ad Al Sa’idi said that ‘Uwaimir bin Ashqar Al Ajilani came to ‘Asim bin Adl and said to him “Asim tell me about a man who finds a man along with his wife. Should he kill him and then be killed by you, or how should he act? Ask the Apostle of Allaah(ﷺ) ‘Asim, for me about it. ‘Asim then asked the Apostle of Allaah(ﷺ) about it. The Apostle of Allaah(ﷺ) disliked the question and denounced it. What ‘Asim heard from the Apostle of Allaah(ﷺ) fell heavy on him. When
Grade: Sahih

Hadith #2246 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sahl bin Sa'd bin Malik; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
‘Abbas bin Sahl reported on the authority of his father “The Prophet (ﷺ) said to ‘Asim bin ‘Adl. Keep the woman with you till she begets the child.
Grade: Hasan

Hadith #2247 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Ja'far bin Ziyad محمد بن جعفر بن زياد; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
Sahl bin Sa’d Al Sa’idi said “I attended the invoking of the curses with the Messenger of Allah (ﷺ) when I was fifteen. He then narrated the rest of the tradition. In this version he said “She then came out pregnant and the child was ascribed to its mother.
Grade: Sahih

Hadith #2248 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Mhmwd bin Khalid محمود بن خالد; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
Sahl bin Sa’ad reported the Apostle of Allaah(ﷺ) as saying – in the tradition of spouses who invoked curses to each other “Look if she bears a child which has very black eyes, large buttocks, I cannot but imagine that he (i.e., ‘Uwaimir) has spoken the truth. But, if she bears a reddish child like the lizard with red spots (waharah), I cannot imagine that ‘Uwaimir has lied against her. She gave birth to a child (like that described the Prophet (ﷺ) ) in a detestable manner.
Grade: Sahih

Hadith #2249 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ayyad bin 'Abdullah عياض بن عبد الله بن عبد الرحمن; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Sahl bin Sa’d Al Sa’idi through a different chain of narrators. This version adds the child was attributed to its mother.
Grade: Sahih

Hadith #2250 - Sunan Abi Dawud - Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin 'Uthman عمرو بن عثمان بن عفان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sahl bin Sa'd bin Malik; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wahb bin Bayan وهب بن بيان (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Sahl bin Sa’d Al Sa’idi through a different chain of narrators. This version has “He divorced her three times before the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) implemented it and what is done before the Prophet (ﷺ) is sunnah(model behavior of the Prophet). Sahl said “I attended this before the Messenger of Allah(ﷺ). Afterwards the sunnah about those who invoked curses on each other was established that they (t
Grade: Sahih

Hadith #2251 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Falayh bin Suliaman فليح بن سليمان; Sahl bin Sa'd bin Malik; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
Sahl bin Sa’ad said “The version of Musaddad has “I witnessed the invoking of curses by the two spouses during the life time of the Apostle of Allaah(ﷺ) when I was fifteen years old. When they finished invoking curses, the Apostle of Allaah(ﷺ) separated them from each other. Here ends the version of Musaddad. Others said “He was present when the Prophet (ﷺ) separated the spouses who invoked curses on each other. The man (Sahl) said “I shall have lied against her, Apostle of Allaa
Grade: Sahih

Hadith #2539 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Musa bin Y'aqub bin 'Abdullah bin Wahb موسى بن يعقوب بن عبد الله بن وهب; Sa'id bin Abi Maryam سعيد بن أبي مريم; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
AbuSalam reported on the authority of a man from the companion of the Prophet (ﷺ). He said: We attacked a tribe of Juhaynah. A man from the Muslims pursued a man of them, and struck him but missed him. He struck himself with the sword. The Messenger of Allah (ﷺ) said: Your brother, O group of Muslims. The people hastened towards him, but found him dead. The Messenger of Allah (ﷺ) wrapped him with his clothes and his blood, and offered (funeral) prayer for him and buried him. They said: Mes
Grade: Da'if

Hadith #3660 - Sunan Abi Dawud - Abdul 'Aziz bin Abi Hazim عبد العزيز بن أبي حازم; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: May Allah brighten a man who hears a tradition from us, gets it by heart and passes it on to others. Many a bearer of knowledge conveys it to one who is more versed than he is; and many a bearer of knowledge is not versed in it.
Grade: Sahih

Hadith #4435 - Sunan Abi Dawud - Abd al-Salam bin Hafs عبد السلام بن حفص; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Sahl bin Sa'd bin Malik; Talq bin Ghanam طلق بن غنام; Uthman bin Muhammad (Sunan Abi Dawud)
I was working in the market. A woman passed carrying a child. The people rushed towards her, and I also rushed along with them. I then went to the Prophet (ﷺ) while he was asking: Who is the father of this (child) who is with you? She remained silent. A young man by her side said: I am his father, Messenger of Allah! He then turned towards her and asked: Who is the father of this child with you? The young man said: I am his father, Messenger of Allah! The Messenger of Allah (ﷺ) then looked a
Grade: Hasan

Hadith #4464 - Sunan Abi Dawud - Abd al-Salam bin Hafs عبد السلام بن حفص; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Sahl bin Sa'd bin Malik; Talq bin Ghanam طلق بن غنام; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone has sexual intercourse with an animal, kill him and kill it along with him. I (Ikrimah) said: I asked him (Ibn Abbas): What offence can be attributed to the animal/ He replied: I think he (the Prophet) disapproved of its flesh being eaten when such a thing had been done to it. Abu Dawud said: This is not a strong tradition.
Grade: Hasan Sahih

Hadith #5148 - Sunan Abi Dawud - Abdul 'Aziz bin Abi Hazim عبد العزيز بن أبي حازم; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sahl bin Sa'd bin Malik (Sunan Abi Dawud)
“three sisters, or three daughter, or two daughter, or two sisters”.
Grade: Da'if